Potenciales beneficios y riesgos de sistemas mini- redes híbridos fotovoltaicos - Martin, Pajuelo Valerio (2018)
Photovoltaic hybrid mini-grid systems (PVHMS) are expected to play a major role in facilitating rural electrification in the developing world, however these systems still face significant barriers to adoption. The technology occupies a middle ground of electrification options e between traditional network extension and individual home systems, possessing elements of each yet also their own distinctive Characteristics. Given this, and their relatively limited application to date, such systems are the focus of a growing body of literature. This work has highlighted a range of potential benefits and risks associated with the technology. However, there still has not been a comprehensive review of these documented benefits and risks; an understanding of which is crucial for informed project investment and implementation decision-making. This paper presents a preliminary review of the existing literature to identify claimed and demonstrated benefits and risks. The most commonly identified benefits are those that are easy to measure: reduced cost and provision of improved electrical services. Other benefits such as the social or environmental benefits are less commonly demonstrated, but are frequently claimed. The major risks identified included incorrect system sizing due to load uncertainty, challenges related to community integration, equipment compatibility issues, inappropriate business models and risks associated with geographical isolation. For all of these types of risks, associated mitigation strategies were also identified in the literature. Further research including industry surveys and additional case studies will be required to validate what has been observed in the literature to date, and identify progress as the technology matures, costs fall and stakeholders learn from these previous experiences.